Hubungan kemampuan berpikir kritis mahasiswa dengan penggunaan media sosial terhadap capaian pembelajaran pada masa pandemi Covid-19 - Bernadetha Nadeak; Citra Puspa Juwita; Elferida Sormin; Lamhot Naibaho (Jurnal Konseling dan Pendidikan, 2020)
Online learning is an option to replace the face-to-face lecture system directly during the Covid-19 pandemic. This choice also coincides with the use of social media to support learning. This condition affects the critical thinking skills of students who are required to survive, adapt in order to attend lectures with the new system, students are required to be skilled in using social media, familiar with the online system so that they can keep up with all learning. This study aims to determine the correlation of critical thinking skills and the use of social media on learning outcomes in the online learning process during the Covid-19 pandemic. The policy of learning from home with online learning using social media such as Facebook, Instagram, and Youtube has become a policy set by the Universitas Kristen Indonesia for the implementation of lectures. This research uses a quantitative approach, with a correlation design conducted online to 254 students who are then analyzed using correlation analysis and multiple correlation analysis. The results showed that there was a positive correlation between (1) critical thinking with student learning outcomes (2) use of social media with student learning outcomes (3) critical thinking and use of social media with student learning outcomes means the results of the study, it can be concluded that there is a correlation between critical thinking and use of social media with student learning outcomes.